THE FRIENDLY TEACHER APPROACH: STRATEGIES TO OVERCOME COMMUNICATION BARRIERS BETWEEN TEACHERS AND STUDENTS - Anik Mufarihah; Suma K. Saleh; Hasrat A Aimang (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
Effective communication between teachers and students is a key element in the learning process. However, at SMP Negeri 5 Luwuk, various communication barriers were found that disrupted the interaction between teachers and students, which had an impact on students' learning outcomes. This research aims to identify these communication barriers and explore the effectiveness of the Friendly Teacher approach as a strategy to overcome them. The research used a qualitative method with a case study approach, involving in-depth interviews with teachers and students, as well as classroom observations. The results show that the Friendly Teacher approach can improve the quality of communication by creating a more open and supportive environment, thereby reducing communication barriers. The findings make an important contribution to the development of more inclusive and effective learning strategies in secondary schools